Adapting the Child and Youth Resilience Measure-Revised for Indonesian Contexts - Ihsana Sabriani Borualogo; Philip Jefferies (Journal of Educational, Health and Community Psychology, 2019)
AbstractThis study describes the adaptation of the Child and Youth Resilience Measure-Revised (CYRM-R) for use in Indonesia. The process of adaptation involved several steps. The first step was translating and back-translating the measurement. The next step was conducting focus groups to explore the legibility of the translated measure. After this, the validity and the reliability of the translated version was tested, as well as an exploration of data. Samples were130 elementary school children (57.7% female) aged 10-13. Data were collected in 2 randomly chosen elementary schools in Kota Bandung. The analyses confirmed the validity and reliability of the measure (alpha = .902). The results indicated that the CYRM-R had been adapted successfully and is a robust measure for exploring the social-ecological resilience of children and youth in Indonesia. The CYRM-R can be used for research and practice in the Indonesian context.Keywords: resilience; child; measurement; cross-cultural; CYRM-R; Indonesia